Translating Al-Hikam Aphorisms: Evaluating Unmarked Topical Themes through Theme-Rheme Structure Analysis - Anis, Muhammad Yunus; Arifuddin, Arifuddin; Khabibi Muhammad Luthfi; Reza Sukma Nugraha; Afnan Arummi; Eva Farhah; Tri Yanti Nurul Hidayati (REiLA : Journal of Research and Innovation in Language, 2024)
Aphorisms are unique literary works known for their memorability, concision, and ambiguity. They have an information structure divided into theme (known information) and rheme (new information), with the "unmarked topical theme" playing a crucial role. This study examines the impact of translation techniques on these unmarked topical themes and their influence on translation quality, focusing on an unexplored area in Arabic discourse. The research design is descriptive qualitative. Data were collected from the aphoristic text of Al-Hikam in Arabic (L1) and its translations into Indonesian (L2a) and Javanese (L2b). The research problems addressed are: (1) What translation techniques do translators employ when dealing with the "unmarked topical theme" in Al-Hikam's aphoristic text? Do translators favor the source language or the target language? (2) How can the translation of unmarked topical themes in Al-Hikam's aphorisms be assessed in terms of accuracy, readability, and acceptability?. The study finds that translation techniques, including conventional equivalent, compensation, modulation, and reduction, significantly impact the translation quality of unmarked topical themes. The conventional equivalent technique is particularly effective in maintaining the position of the unmarked topical theme from the source language to the target language. This research contributes to developing an Arabic translation model based on Systemic Functional Linguistics (SFL) analysis. It also provides a comparative analysis of the distinctive discourse topic development elements in Arabic, Indonesian, and Javanese texts, highlighting the implications of various translation techniques on the quality of aphoristic translations.